2017
DOI: 10.1021/acs.oprd.7b00254
|View full text |Cite
|
Sign up to set email alerts
|

Match-Making Reactors to Chemistry: A Continuous Manufacturing-Enabled Sequence to a Key Benzoxazole Pharmaceutical Intermediate

Abstract: The focus of this study was to develop a chemical reaction sequence toward a key benzoxazole building block, required for clinical manufacturing of a lead candidate in the respiratory disease area. The chemistry consisted of initial low-temperature reactions with an organometallic reagent to generate the benzoxazole core, and was followed by noncryogenic transformations toward a sulfonamide substituent. With particular interest in continuous-flow manufacturing we attempted to integrate the entire sequence on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Copyright 2020 American Chemical Society), ( e ) the two CSTRs-in-series system used in the synthesis of benzoxazole from N-pivaloyl 3,4-dichloro aniline (Reproduced with permission from Ref. [ 26 ]. Copyright 2017 American Chemical Society.…”
Section: Cstrs-in-seriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Copyright 2020 American Chemical Society), ( e ) the two CSTRs-in-series system used in the synthesis of benzoxazole from N-pivaloyl 3,4-dichloro aniline (Reproduced with permission from Ref. [ 26 ]. Copyright 2017 American Chemical Society.…”
Section: Cstrs-in-seriesmentioning
confidence: 99%
“…Susanne et al [ 26 ] reported the synthesis of benzoxazole from N-pivaloyl 3,4-dichloro aniline. In this case, two steps utilized CSTRs-in-series systems (Fig.…”
Section: Cstrs-in-seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of the products of DoM can be very high given the ability to tolerate halogens and other reactive functional groups while increasing complexity. Such metalations are becoming commonplace in the pharmaceutical and fine chemical industries and can often be executed using continuous processing methodology as a practical means to access low temperatures at large scale …”
mentioning
confidence: 99%